Age-performance profiling in elite breaststroke swimmers: career quantitative model - Dopsaj, M.; Šiljeg, K.; Zoreti, D. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION: The modeling procedure represents the process of objectifying the most likely outcome of the observed phenomenon. One of the problems in the sports training system is the recognition of the chronological age-result potential for top performance achievements as a function of the career duration of elite athletes. The aim of this study is to profile the possible ultimate chronological limits of career performance in 50m pool at elite breaststroke swimmers, and to numerically define the characteristics of a given age trajectory model of career best performance.